BIOLOGI Ooencyrtus malayensis Ferr. PARASITOID TELUR Dasynus piperis China, PADA INANG ALTERNATIF Nezara viridula L. - ASNIMAR ALWI; DECIYANTO SOETOPO (Pusat Penelitian dan Pengembangan Perkebunan, 2000)
Biology of egg parasitoid ('Ooencyrtus malayensis Ferr.) ofpepper bug on alternate egg host (Nezara viridula L)Pepper bug (Dasynus piperis China) is an important pest of pepper. The pest widely spread in most pepper plantations of Indonesia. The level of the pest attack varied depended on crop cultivation treatment. Ooencyrtus malayensis is one of natural enemies which is able to control the population of pepper bug in plantation. The objective of this research was to study some aspects of the egg parasitoid biology by using eggs of Nezara viridula as the alternate host. This research was designed in a completely randomized block with four replicates. Dasynus piperis was collected from Bangka island and reared in Laboratory of the Research Institute for Spice and Medicinal Crops (RISMC ). Nezara viridula was fed with cowpea bean. This reascarch was conducted from July 1998 to February 1999. Experiment was divided into seven steps such as oviposition. pre adult period, production of parasitoid per host egg. egg preference, infestation period effect of cold storage (4°C) and parasitoid population. Research results showed that there were 85.5 parasitoid produced during its life time. Pre adult period lasted from 12 to 16 days, alternate host produced 3 parasitoids. The parasitoid pefeed the host of 0-2 days old. The eggs could be stored for 25 days in a efrigenerator (4°C). The longer the infestation and the larger number of parsitoid infested the larger numbers of parasitoid produced.